CEDIL Work-in-Freedom 2 Bangladesh Migration Dataset - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This survey is part of a broader evaluation study that supports the Foreign Commonwealth and Development office, United Kingdom (formerly DFID) funded program Work in Freedom Phase 2 (WiF-2), the International Labor Organization (ILO) has implemented between 2018 and 2023. WiF-2 aims "to reduce vulnerability to trafficking and forced labor of women and girls across migration pathways leading to the care sector and textiles, clothing, leather and footwear industries (TCLFI) of South Asia and the Arab States" (TOC WiF-2). Forced migration includes deceptive or coercive recruitment, abuse of vulnerable situations, exploitative conditions of work, coercion at the destination, and abuse of vulnerability at the destination. The program aims to reach at least 350,000 women and girls at source in India, Nepal, Bangladesh, and at destinations in Oman, Bahrain, Lebanon, and Jordan.